(untitled) (Journal on studies and research of academic knowledge, 2021)
An increase in the incidence of the false smut of rice caused by the fungus Ustilaginoides virens has been observed in the last years on the most sown variety IRGA 424 in various producing regions in Paraguay. The majority of the fungicides currently used in the country are recommended for leaf spots and rice blast and for this reason the objective of this study was to determine the efficiency of a combination of fungicides applied at different phenological stages for the rice false smut control. The combination of two commercial fungicides was evaluated, Azoxistrobin 20 % + Difenoconazol 12,5 % with a dosage of 400cc/ha, on plots with natural infection of the disease. The application was made on the following growth stages: R1; R2; R3; R4; R4+R6; R2+R3; R3+R4; R2+R3+R4; R1+R2+R3+R4+R6, totalizing 10 treatments including a non-protected control. The results show that 2 applications made on the stages R2+R3; R3+R4 and 5 applications on R1+R2+R3+R4+R6 reduced numerically the incidence of the disease by 85, 89 and 81 % respectively, compared to the non-protected control. Yield was increased up to 28% on treated plots. From an economic point of view, the application of the fungicide at 2 reproductive stages is sufficient for the management of the disease.